2005
DOI: 10.1523/jneurosci.3036-04.2005
|View full text |Cite
|
Sign up to set email alerts
|

Ensemble Coding of Vocal Control in Birdsong

Abstract: Zebra finch song is represented in the high-level motor control nucleus high vocal center (HVC) (Reiner et al., 2004) as a sparse sequence of spike bursts. In contrast, the vocal organ is driven continuously by smoothly varying muscle control signals. To investigate how the sparse HVC code is transformed into continuous vocal patterns, we recorded in the singing zebra finch from populations of neurons in the robust nucleus of arcopallium (RA), a premotor area intermediate between HVC and the motor neurons. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
248
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(264 citation statements)
references
References 34 publications
13
248
3
Order By: Relevance
“…These functional groups are distinct and composed of an unexpectedly small number of neurons. The discrete organization that we see, which differs from previously observed distributed activity 4,18,30 , is made apparent by the ability to evoke simple motor patterns with controlled visual stimulation. The fact that more complex behaviors are associated with distributed activation of many neurons is consistent with a model in which subsets of neurons initiate distinct components of the behavior 31,32 .…”
Section: Discussioncontrasting
confidence: 66%
“…These functional groups are distinct and composed of an unexpectedly small number of neurons. The discrete organization that we see, which differs from previously observed distributed activity 4,18,30 , is made apparent by the ability to evoke simple motor patterns with controlled visual stimulation. The fact that more complex behaviors are associated with distributed activation of many neurons is consistent with a model in which subsets of neurons initiate distinct components of the behavior 31,32 .…”
Section: Discussioncontrasting
confidence: 66%
“…Plotted are the average FFs during these periods, divided by the average values across all UD songs for each male, for 3 syllables that showed significant changes inlable structure and sequencing (Bottjer et al 1984;Kao et al 2005;Ö lveczky et al 2005;Scharff and Nottebohm 1991). Furthermore, the variability of spiking activity in LMAN is reduced during renditions of FD song, which could serve to reduce the variability of firing in RA and, consequently, syllable structure (Hessler and Doupe 1999;Kao et al 2005;Leonardo and Fee 2005;Ö lveczky et al 2005). This causal relationship is supported by the finding that introducing variable amounts of activity into LMAN increases the variability of syllable structure (Kao et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Separate medial and lateral basal ganglia circuits project to different areas of the vocal motor pathway, and it has been proposed that the lateral pathway, which includes LMAN and projects to RA, regulates syllable variability, whereas the medial pathway, which includes the medial nucleus of the nidopallium (MMAN) and projects to HVC (proper name), regulates sequence variability (Foster et al 1997;Jarvis et al 1998;Kubikova et al 2007;Reiner et al 2004). Mounting evidence indicates that HVC and its afferents are critically involved in sequence generation for song (reviewed in Fee et al 2004;Hahnloser et al 2002;Hosino and Okanoya 2000;Vu et al 1994;Yu and Margoliash 1996) and that RA is important for the acoustic structure of syllables (Leonardo and Fee 2005;Vu et al 1994;Yu and Margoliash 1996); therefore, the distinct connectivity of the medial and lateral basal ganglia circuits to the vocal motor pathway is consistent with such differential contributions to syllable sequencing versus structure. Further support for this notion comes from the observation that IEG expression in the lateral but not the medial pathway is modulated by social context in the zebra finch, a species in which there is substantial evidence for context-dependent changes in adult syllable structure but not in syllable sequencing (Jarvis et al 1998;Kao and Brainard 2006;Kao et al 2005; but see Sossinka and Böhner 1980).…”
Section: Discussionmentioning
confidence: 99%
“…experimentalists [6,27] and assumed in several theoretical studies [28,29,30]. In a recent experiment [26], calcium imaging and timing studies of intracellular recordings have suggested the existence of synfire chains in the visual cortices of mice and cats but no similar imaging study has yet been carried out for songbirds.…”
Section: A a Homogeneous 1d Chain Of Excitatory Neuronsmentioning
confidence: 99%